Metabolic-stress-induced mitochondrial calcium dysregulation: a central hub in diabetic cardiomyopathy pathogenesis and treatment - Deng, Siqi; Tayefi, Fatemeh; Jin, Yunpeng (Frontiers in Endocrinology, 2025)
Diabetic cardiomyopathy (DCM), as a devastating complication of diabetes mellitus (DM), arises from a complex interplay between systemic metabolic derangements and myocardial vulnerability. While hyperglycemia, lipotoxicity, and insulin resistance are established drivers of cardiac dysfunction, the precise mechanisms linking these metabolic insults to cardiac dysfunction remain elusive. Recent evidence suggests that the dysregulation of mitochondrial calcium homeostasis plays a critical role in integrating diabetic metabolic stress and cardiomyocyte fate. This review synthesizes recent advances in understanding how mitochondrial calcium mishandling—encompassing impaired uptake, excessive release, and buffering failure—orchestrates the pathological triad of bioenergetic deficit, oxidative stress, and cell death in DCM. We delve into the molecular mechanisms underpinning this dysregulation, highlighting its interplay with the diabetic metabolic milieu. Furthermore, we critically evaluate novel therapeutic strategies targeting mitochondrial calcium fluxes, including the inhibition of the mitochondrial calcium uniporter (MCU), the activation of the mitochondrial Na+/Ca2+/Li+ exchanger (NCLX), and the modulation of the mitochondrial permeability transition pore (mPTP), discussing their clinical translation potential and existing challenges. By reframing DCM through the lens of mitochondrial calcium homeostasis, this review not only synthesizes current knowledge but also provides a critical comparison of emerging therapeutic strategies and evaluates the formidable challenges in their clinical translation, thereby bridging the gap between endocrine metabolism and cardiac pathophysiology and offering nuanced perspectives for biomarker discovery and stage-specific interventions.